2022
DOI: 10.1002/adhm.202201367
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Synergistic Design of Bi‐Layered Double Hydroxides Modified Magnesium Alloy toward Multifunctional Orthopedic Implants

Abstract: Magnesium (Mg)-based alloys have been regarded as promising implants for future clinic orthopedics, however, how to endow them with good anti-corrosion and biofunctions still remains a great challenge, especially for complicated bone diseases. Herein, three transition metals (M = Mn, Fe, and Co)-containing layered double hydroxides (LDH) (LDH-Mn, LDH-Fe, and LDH-Co) with similar M content are prepared on Mg alloy via a novel two-step method, then systematic characterizations and comparisons are conducted in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…In another study, Mn-based LDH was identified to possess better corrosion resistance in comparison with Fe-based LDH and Co-based LDH (Figure 4g). [147] The released metal cations and interlayer anions depending on the degradation behaviors contribute to the bioactivity of LDHs. As an alkaline 2D nanomaterial, LDHs possess acidresponsive degradation properties and tend to degrade faster in acidic environments, which benefits targeted drug delivery as acidic or H 2 O 2 -riched microenvironment is more commonly observed in bone infections, bone tumors, and osteoarthritis circumstances.…”
Section: The Mechanical Corrosion Resistance and Degradation Properti...mentioning
confidence: 99%
See 3 more Smart Citations
“…In another study, Mn-based LDH was identified to possess better corrosion resistance in comparison with Fe-based LDH and Co-based LDH (Figure 4g). [147] The released metal cations and interlayer anions depending on the degradation behaviors contribute to the bioactivity of LDHs. As an alkaline 2D nanomaterial, LDHs possess acidresponsive degradation properties and tend to degrade faster in acidic environments, which benefits targeted drug delivery as acidic or H 2 O 2 -riched microenvironment is more commonly observed in bone infections, bone tumors, and osteoarthritis circumstances.…”
Section: The Mechanical Corrosion Resistance and Degradation Properti...mentioning
confidence: 99%
“…Segura-Pérez et al [221] reported a novel bone implant composed of HA and LDHs with different metal compositions, where significant bacteriostatic effects against clinical multi-resistant bacteria under a very low minimum inhibitory concentration (0.5 mg mL −1 ) were observed in Cu-based LDHs. Zhang et al [147] compared the antibacterial efficiency of Mg alloy coated with Mn-based LDH, Fe-based LDH, and Co-based LDH. It turned out that Fe-based LDH possessed the best antibacterial properties and Mn-based LDH revealed excellent photothermal and enzymatic activities.…”
Section: The Intrinsic Antibacterial Properties Of Ldhsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies [201] propose to formation of multilayer LDH coatings with different effects on implantable magnesium alloys. Thus, the lower layer of Mn‐LDH adjacent to the metal plate provides corrosion protection for the implant, and iron‐saturated Fe‐LDH external layer provides high biocompatibility and antimicrobial properties; at the same time, metal ions released during the slow decomposition of LDH have a positive effect on angiogenesis and osteogenesis.…”
Section: Applications Of Layered Double Hydroxidesmentioning
confidence: 99%